Pengaruh Strategi Kompetitif Dan Lingkungan Eksternal Pada Kinerja Umkm Di Yogyakarta - Ghofat, Abdul; Sunaryo, Kunti (208-7721)
Micro, small and enterprises (SMEs) is one of the most crucial of economic development and local communities. For driving the economy, SMEs must be able to survive in an increasingly competitive business competition. This study examines influence of the external environment and competitive strategies on performance of SMEs in Yogyakarta. Competitive strategy used in this study is Porter generic strategies are cost leadership and differentiation, while the external environment used is environment dynamism and environment hostility. Based on 106 respondents who responded to the questionnaire, the results showed that cost leadership affects the performance of SMEs in Yogyakarta, but differentiation strategy doesnât effect on the performance of SMEs in Yogyakarta. Differentiation strategy doesânt effect on performance of SMEs because there is less supported by the SME workforce skilled in applying innovation to improve its performance. The other results in this study are environment dynamism is not a variable that moderates the relationship strategy to performance of SMEs, while environment hostility is variable that moderates the relationship cost leadership to performance of SMEs but is not a variable that moderates the relationship differentiation to performance of SMEs